STANDARDIZED SUPERCRITICAL CO2 EXTRACT OF ACANTHUS ILICIFOLIUS (LINN.) LEAVES INHIBITS THE PRO-INFLAMMATORY CYTOKINE TUMOR NECROSIS FACTOR-Î‘ IN LIPOPOLYSACCHARIDE-ACTIVATED MURINE RAW 264.7 MACROPHAGE CELLS - Arumugam, Saranya; Thiruganasambantham, Ramanathan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Acanthus ilicifolius Linn. (Acanthaceae) is a medicinal mangrove plant used in the treatment of inflammation. Previous phytochemical studies have identified 2-benzoxazolinone (BOA) from the leaves of A. ilicifolius. In the present study, we attempted to standardize the supercritical CO2 leaf extract of A. ilicifolius (SCFE-AI) for BOA content and investigate the tumor necrosis factor-Î± (TNF-Î±) inhibitory effect of SCFE-AI and BOA on the lipopolysaccharide (LPS)-induced inflammation in RAW 264.7 macrophages. The acute oral toxicity of SCFE-AI and BOA was also established. Methods: SCFE-AI was standardized for BOA content using high-performance thin-layer chromatography (HPTLC) method. The cytotoxicity of SCFE-AI and BOA was evaluated using MTS colorimetric method. The in vitro anti-inflammatory effect of SCFE-AI and BOA on TNF-Î± production in LPS-activated RAW 264.7 cells was quantified using ELISA method. Acute oral toxicity studies were performed following the Organization for Economic Co-operation and Development test guideline No. 423. Results: The amount of BOA was found 0.8% w/w of SCFE-AI. The RAW 264.7 cell viability was unaffected by SCFE-AI and BOA treatments within a concentration range <1000 mg/ml after 24 h incubation. SCFE-AI decreased the production of TNF-Î± in a dose-dependent manner compared to BOA. The LD50 value for SCFE-AI was found to be >2000 mg/kg and ranges from 300 to 2000 mg/kg with BOA. Conclusion: The HPTLC chromatogram could serve as an analytical tool for authentication and quantification of BOA content. The anti-inflammatory mechanism of A. ilicifolius might be through the inhibition of TNF-Î± production.